Protection of agricultural land in light of the reform of the spatial planning system of 7 July 2023 - Marciniuk, Konrad (Przegląd Prawa Rolnego, 2025)
This article aims to assess the impact of the reform of the spatial planning system on the legal protection of agricultural land. The analysis focuses primarily on the protection of agricultural land resources in the context of the introduction of a new type of planning document into the Polish legal system, namely the general municipal plan, and, on the other hand, significant changes concerning the location of investments based on individual location decisions (decisions on building conditions). The author concludes that the thorough overhaul of the spatial planning system in Poland which began in 2023 has tightened the regime for the protection of agricultural land by limiting the possibility of allocating agricultural land for non-agricultural purposes in areas not covered by local spatial development plans. It also increased the predictability of decisions made in local plans by subordinating them to general municipal spatial development plans. This solution should contribute to more effective rural spatial planning, including the reduction of spatial conflicts resulting from the juxtaposition of areas with different functions.